Digital equity : Issues and models - Shafie, Halim (Universiti Utara Malaysia, 2002)
Digital equity is normally referred to as the quick, easy, and appropriately functional access to Information and Communications Technologies (ICT) equipment and tools (e.g. computers, telephones and the internet), as well as access to training to ensure effective access and use. The use of the word "access" is to highlight that ownership does not necessarily equate with use, and therefore, ownership of household ICT does not necessarily mean that all individuals within that household own or use the technology. This implies that the statistical figures on such matters must be interpreted with extra caution.